Industry and Social Change In Majalengka - Mulyadi, Hendra (Al-Makki Publisher, 2023)
Majalengka Regency is a potential industrial destination for economic players both on a macro and micro scale. The indication of industrial interest is marked by the switch of several factories or companies in the Karawang, Cikarang and Bekasi regions that build branches of production sources in this region. With consideration of income and its outcomes on the progress of the company, attracting local and foreign investors competing to advance every line of business that is pioneered and developed. In less than 2 years, this phenomenon underlies the basis for a shift in the social dynamics of the Majalengka regency community along with the development of industry in the region. In the course of the business world, both macro and micro entrepreneurs always improve every strategy to capture the maximum income and reduce any ineffective expenses. In the struggle and competition of the strategy, there is a decrease in the effectiveness of local entrepreneurs who are starting to be marginalized and starting to go out of business